The association between estimated pulse wave velocity and cardio-cerebrovascular disease risk: a cohort study - Guangyan Liu; Wenyue Sha; Yueying Wu; Jinhua Luo; Yuying Cai; Tuming Zhang; Yu Yang (European Journal of Medical Research)
Abstract Background Various measures of arterial stiffness have been linked to the risk of cardiovascular disease. However, the relationship between the estimated pulse wave velocity (ePWV), a novel indicator of arterial stiffness, and cardio-cerebrovascular disease risk remains unclear. This study investigated the relationship between the ePWV and the risk of cardio-cerebrovascular diseases. Methods A total of 17,708 participants aged 45 years and older enrolled in the China Health and Retirement Longitudinal Study (CHARLS), conducted between 2011 and 2012, and participants with a 7-year follow-up were included. Ultimately, 8242 respondents were included in the study. The ePWV was calculated using age and mean blood pressure. Cardio-cerebrovascular diseases, including myocardial infarction, cerebral infarction, and intracerebral haemorrhage, were categorised as cardiovascular and cerebrovascular diseases. Clinical and demographic characteristics were collected. A Cox proportional hazards model was used to explore the relationship between ePWV and the risk of cardiovascular disease. Results During the 7-year follow-up, 21.7% of the participants (1791/8242) developed cardio-cerebrovascular diseases. After adjusting for potential confounding factors, the ePWV was positively associated with the risk of cardio-cerebrovascular disease (adjusted hazard ratio: 1.16, 95% CI 1.11–1.22, P < 0.001). The ePWV was divided into quartiles, and regression analysis was performed. Participants in the highest ePWV quartile had a 128% higher risk of cardio-cerebrovascular disease than those in the lowest quartile. The subgroup analysis showed that the positive association between the ePWV and the risk of cardio-cerebrovascular disease remained consistent among middle-aged and older adults across different Chinese communities. Conclusions In middle-aged and older Chinese adults, the ePWV was significantly and positively associated with the risk of cardio-cerebrovascular disease, making it a reliable and innovative predictor of these conditions.